USING CHATGPT IN ENGLISH LANGUAGE LEARNING: HOW MALAYSIAN POLYTECHNIC STUDENTS VIEW IT - Lam Kok Wei,; Salmiza Abdul Rahim, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The study explores Malaysian polytechnic students’ perceptions on using the increasingly popular ChatGPT (a large language model chatbot created by OpenAI) in their English language learning. The objectives of the study include determining to what extent ChatGPT is used in students’ English language learning, and how students perceive about using ChatGPT in helping them learn English language. The research design employed in this study is a survey study, and specifically a cross-sectional survey. For this purpose, a set of questionnaire adapted from relevant studies was distributed to diploma-level students in a Malaysian polytechnic. The results of this preliminary study will provide useful insight into how ChatGPT can benefit both formal and informal English language learning.